Are Health Care Providers Caring for Pregnant and Postpartum Women Ready to Confront the Perinatal Cannabis Use Challenge? - Kitsantas, Panagiota; Pursell, Shannon R. (American Journal of Perinatology, 2023)
Objective The purpose of this study was to assess health care providers' knowledge and practices related to cannabis use among pregnant and postpartum women.Study Design A survey of health care providers (n = 75 responders) was conducted across four main regions in the state of Virginia to assess knowledge of adverse health effects associated with perinatal cannabis use, screening tools, follow-up for positive screening, barriers to having discussions about cannabis use, and treatment among pregnant and postpartum women.Results An astonishing 34.7% of the providers surveyed responded as not being aware of the impacts of cannabis use on the health of the mother and infant, and 66.7% of them reported that they would like some training on feeling comfortable with their knowledge about the impact of perinatal cannabis use on the population they are serving. When asked about providing resources and/or patient education related to cannabis use during pregnancy and/or breastfeeding, 62.7% reported they did not but they would be interested in providing both resources and education. Over one-third of the providers did not have a follow-up process for positive screening. In addition, numerous barriers to asking/screening and/or discussing cannabis use and potential harm reduction methods for the pregnant and postpartum populations emerged such as inadequate or lack of resources for positive screening, lack of knowledge on the topic, unsure about the policies of reporting a positive screening, etc.Conclusion The findings of this study indicate that health care providers caring for pregnant and postpartum women are not equipped to make appropriate recommendations to patients and guide them through decision-making. Health care providers caring for pregnant and postpartum women need to be knowledgeable on how to best support patients with cannabis use for effective counseling and guidance due to health risks. State policies and resources are needed to ensure training for clinicians on perinatal cannabis.Key Points
Keywords: perinatal cannabis use; pregnancy; postpartum; health care providers